Perceived Discrimination and Social Relationship Functioning among Sexual Minorities: Structural Stigma as a Moderating Factor. Issue 1 (6th November 2015) - Doyle, David Matthew; Molix, Lisa
Abstract : Work on structural stigma shows how public policy affects health outcomes for members of devalued groups, including sexual minorities. In the current research, structural stigma is proposed as a moderating variable that strengthens deleterious associations between perceived discrimination and social relationship functioning. Hypotheses were tested in two cross‐sectional studies, including both online (N = 214; Study 1) and community (N = 94; Study 2) samples of sexual minority men and women residing throughout the United States. Structural stigma was coded from policy related to sexual minority rights within each state. Confirming hypotheses, support for the moderating role of structural stigma was found via multilevel models across studies. Specifically, associations between perceived discrimination and friendship strain, loneliness (Study 1) and familial strain (Study 2) were increased for those who resided in states with greater levels of structural stigma and attenuated for those who resided in states with lesser levels. In Study 1, these results were robust to state‐level covariates (conservatism and religiosity), but conservatism emerged as a significant moderator in lieu of structural stigma in Study 2. Results are discussed in the context of the shifting landscape of public policy related to sexual minority rights within the United States.